Enhancing and predicting digital consumer behavior with AI - Musiolik, Thomas Heinrich 1980-; Villamarin Rodriguez, Raul; Kannan, Hemachandran 1985- (IGI Global, 2024)
Understanding consumer behavior in today's digital landscape is more challenging than ever. Businesses must navigate a sea of data to discern meaningful patterns and correlations that drive effective customer engagement and product development. However, the ever-changing nature of consumer behavior presents a daunting task, making it difficult for companies to gauge the wants and needs of their target audience accurately.Enhancing and Predicting Digital Consumer Behavior with AI offers a comprehensive solution to this pressing issue. A strong focus on concepts, theories, and analytical techniques for tracking consumer behavior changes provides the roadmap for businesses to navigate the complexities of the digital age. By covering topics such as digital consumers, emotional intelligence, and data analytics, this book serves as a timely and invaluable resource for academics and practitioners seeking to understand and adapt to the evolving landscape of consumer behavior.
Keywords: Artificial intelligence; Consumer behavior -- Technological innovations; Electronic commerce -- Technological innovations